2011
DOI: 10.1103/physrevb.83.104105
|View full text |Cite
|
Sign up to set email alerts
|

Structural transformation in magnetite below the Verwey transition

Abstract: The magnetite structure was studied with synchrotron x-ray powder diffraction above and below the Verwey transition. A symmetry-mode analysis was performed to obtain the atomic displacements from the amplitudes of condensing modes. The main contributing modes that drive the structural phase transition at the Verwey temperature correspond to the irreducible representations 5 , X 1 , X 4 , W 1 , and W 2 . The W modes, neglected so far, must be taken into account so a reliable description of the low-temperature c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
77
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 36 publications
6
77
1
Order By: Relevance
“…The Rietveld full pattern fitting yields the following lattice parameters: a = 8.3954(12) Å and 8.3976(28) Å for BSFC24 and BSFP24, respectively. These values are slightly higher than the data for ideal magnetite (a = 8.39457(1) Å [37]). The attempt to calculate the degree of crystallinity using the amorphous background and the large peaks located at 23, 45, and 60, is basically questionable because the amorphous glassy matrix, which consists mainly in light elements (Si, B, Na), and the crystalline magnetite have different atomic scattering factors.…”
Section: Phase Structurecontrasting
confidence: 39%
“…The Rietveld full pattern fitting yields the following lattice parameters: a = 8.3954(12) Å and 8.3976(28) Å for BSFC24 and BSFP24, respectively. These values are slightly higher than the data for ideal magnetite (a = 8.39457(1) Å [37]). The attempt to calculate the degree of crystallinity using the amorphous background and the large peaks located at 23, 45, and 60, is basically questionable because the amorphous glassy matrix, which consists mainly in light elements (Si, B, Na), and the crystalline magnetite have different atomic scattering factors.…”
Section: Phase Structurecontrasting
confidence: 39%
“…Below T CO this electron is localized on the iron sites, impeding its mobility. However, it has been later demonstrated that this Verwey CO model is at odds with the experimental facts in Fe 3 O 4 because the charge distribution is not bimodal and the maximum charge disproportionation found is much lower than one electron [13,14]. On the other hand, the CO transition in LuFe 2 O 4 was considered to originate electrical dipoles in the geometrically frustrated triangular Fe lattice that would give rise to ferroelectricity [15].…”
Section: Introductionmentioning
confidence: 77%
“…The decrease of the conductivity is due to a freezing of the electron hopping between different octahedral Fe sites, causing a charge disproportionation that results in two types of Fe B atoms acting with a slightly enhanced (Fe 3+ ) or reduced (Fe 2+ ) valence. The distribution of the different Fe B atoms at the unit cell configures the charge order (CO), intimately linked to the orbital order 5,6 , and determines the full monoclinic Cc symmetry [7][8][9][10][11] . Decades of efforts have been devoted to the understanding of the VT 12,13 , and yet some puzzling fundamental aspects remain unanswered, such as the structural or electronic origin of the transition, or the extent of the short range order above T V .…”
Section: Introductionmentioning
confidence: 99%